STRATEGI DIPLOMASI PEMERINTAH THAILAND DALAM MEMPROMOSIKAN PARIWISATA GAY PADA TAHUN 2015-2022 - Nora Dameris Manurung; Indra Pahlawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research is intended to determine the impact and results of the Thai government's diplomatic strategy in promoting gay tourism in 2015–2022, where Thailand is a country that recognizes the existence of and protects gays through law, even though it was initially rejected. There are many strategies carried out by the Thai government to promote gay tourism. This research is analyzed using the level of analysis of the nation-state, the perspective of konstructivism, the concept of queerness, and the theory of public diplomacy by Nicholas J. Cull. The method used in this research is qualitative. The data collection technique for this research was a literature study of several books, journals, articles, news articles, documents, and websites. From the results of this research analysis, it can be concluded that the various strategies undertaken by the Thai government to promote gay tourism are successful. According to the listening indicator, Thailand heard from foreign tourists that there were no gay-friendly free places, so the government created gay-friendly tourism. According to the advocacy indicator, Thailand conducted hearings, campaigns, communications, and agreements with foreign communities. The indicators of cultural diplomacy are proven by promotion through cultural festivals and special events for LGBT people. According to the indicators of exchange diplomacy, it is carried out through agents or tour guides. As well as from indicators of international branding carried out through technology such as the internet, television, radio, and so on, so that many films, dramas, television shows, and several social media platforms have gained many fans. Keywords: Diplomacy, Promoting, Gay Tourism, Thailand